Sequential two-level information protection with probability reliability - Журиленко, Борис Євгенович; Ніколаєв, Кирило Іванович (Ukrainian Information Security Research Journal, 2020)
In this work, theoretical studies of the physical hacking process for sequential two-level technical protection of information (TPI) with probabilistic reliability are carried out. The research uses an approach related to the reliability of various equipment, technical devices and systems, which have been studied in sufficient detail and have provided good practical results with a quantitative probabilistic assessment. To calculate and evaluate the possibilities of sequential two-level technical information protection, we used single-level TPI with probabilistic reliability, proposed and considered in the works of B. Zhurilenko. In this work, we used the method of constructing a consistent two-level technical protection of information with probabilistic reliability and the possibility of comparing it with equivalent single-level protection. Such a comparison can be useful in assessing and comparing multilevel TPI, since such an approach will make possible evaluation of different structures of multilevel protection systems and it is quite simple to compare the designed and existing TPI from a uniform point of view. Studies have shown that the distribution surface of the maximum probabilities of breaking into an equivalent single-level TPI does not completely coincide with the distribution of the probability maxima of breaking into a two-level TPI. Therefore, protection comparisons are only possible in the hacking direction selected for analysis. To analyze and compare the security of information in other directions, it is necessary to calculate and construct the distribution of the maximum probabilities of breaking for these directions using the proposed methodology. The paper proposes a method for determining the real probability of breaking a two-level protection not by the maximum value of the probability of breaking, but by the distribution of the probability of breaking a sequential two-level TPI, since breaking of TPI may not necessarily occur at the maximum values of the probability of breaking. In this case, based on the constructed surfaces of the probabilities of breaking, the real reliability of the TPI can be determined for any direction of breaking.